Penerapan Metode Diagram Fishbone untuk Identifikasi Masalah Kualitas Layanan di StartUp Parfum Foxsniff - Muhammad Puja Dwi Surya; Muhammad Hafidz Azizi; Muhammad Iqbal; Satrio Rasendriya Widyahana; Farraz Ariel Gumita; Amer Abdul Aziz (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to identify and analyze service quality issues in the Foxxsniff perfume startup using the Fishbone diagram method. A qualitative descriptive approach is employed with data collection techniques through observation, in-depth interviews, and documentation studies. Data analysis utilizes check sheets, pareto charts, and fishbone diagrams. The research results are expected to identify service quality dimensions that require improvement and their root causes. The implementation of the Fishbone method in service quality management is expected to contribute to the development of service quality improvement strategies for the Foxxsniff perfume startup.